Speed measurements in wheelchair sports - theory and application - Fuss, F. K. (Sports Technology, 2012)
Speed measurements should be the standard in high-performance wheelchair sports, specifically for track racing. The required technology (triaxial gyroscopes and data logger) is nowadays no longer an obstacle, as smartphones are ubiquitous. Based on gyroscope raw data, in particular data obtained from smartphones attached to the wheels, the following performance parameters can be calculated: the true wheel speed, turning speed and sense, turning radius and linear wheelchair speed. The true wheel speed is obtained from the kinematics of a planetary bevel gear. Based on speed profiles, weak points, such as discontinuous acceleration and sudden drops in velocity, can be identified. Further performance parameters are calculated from speed profiles, such as peak acceleration, consistency of push frequency, push and recovery time and ratio of push to recovery time. Furthermore, speed profiles provide the basis for simulating winning times, if the speed profile is optimised (changing weak points to the ideal speed profile), or wheelchair parameters are changed, such as drag coefficient, rolling friction coefficient or mass.